Successful Management of a Neglected Case of Nephropathic Cystinosis - Mohamed A. El-Naggari; Ibtisam Elnour; Hussein Al-Kindy; Aamir Al-Shahrabally; Anas A. Abdelmogheth (Sultan Qaboos University Medical Journal, 2014)
Cystinosis is a rare metabolic disorder characterised by lysosomal cystine accumulation leading to multi-organ damage; clinically, the kidneys are the first organ affected. Respiratory insufficiency caused by overall respiratory muscle myopathy is a life-threatening complication. Treatment with cysteamine should be initiated rapidly and continued lifelong to prolong renal function and protect the extra-renal organs. We report the case of a four-year-old Omani girl, diagnosed with infantile nephropathic cystinosis at 21 months. Cysteamine was prescribed but with no compliance to medications. She presented to the Child Health Department of Sultan Qaboos University Hospital, Oman, two years later with severe failure to thrive, electrolyte disturbance and respiratory failure. The hypoventilation and early respiratory dysfunction, due to intercostal and diaphragm myopathy, was treated by non-invasive positive-pressure ventilation. The patient was discharged after four months of intensive rehabilitation with no ventilator support. No standard treatment options have yet been established for respiratory dysfunction in cystinosis.